A Case Study of Dementia: Self-Learning Module (Out of Print) - Martin Klapheke (Association of American Medical Colleges, 2012)
Abstract This resource for third-year medical students is a self-learning module on dementia which demonstrates the evolution of a clinical case from presentation to follow-up over 5 years. It can be viewed on any computer and the instructor/student can navigate at-will through the interactive quizzes, text, and imbedded video clips. The focus is on differential diagnosis and treatment planning, with intermittent self-assessment quizzes and references to American Psychological Association Practice Guidelines and other evidenced-based literature, for further study. Based on student and faculty feedback on the length of the module, the audio narration, video clips, and text have been shortened. It now takes approximately 30 minutes to complete the module, but the length of the session will be longer if it is used for small-group discussion and interaction.